Simulation-based Randomized Comparative Assessment of Out-of-Hospital Cardiac Arrest Resuscitation Bundle Completion by Emergency Medical Service Teams Using Standard Life Support or an Experimental Automation-assisted Approach. Issue 6 (December 2016) - Choi, Bryan; Asselin, Nicholas; Pettit, Catherine C.; Dannecker, Max; Machan, Jason T.; Merck, Derek L.; Merck, Lisa H.; Suner, Selim; Williams, Kenneth A.; Jay, Gregory D.; Kobayashi, Leo
Abstract : Introduction: Effective resuscitation of out-of-hospital cardiac arrest (OHCA) patients is challenging. Alternative resuscitative approaches using electromechanical adjuncts may improve provider performance. Investigators applied simulation to study the effect of an experimental automation-assisted, goal-directed OHCA management protocol on EMS providers' resuscitation performance relative to standard protocols and equipment. Methods: Two-provider (emergency medical technicians (EMT)-B and EMT-I/C/P) teams were randomized to control or experimental group. Each team engaged in 3 simulations: baseline simulation (standard roles); repeat simulation (standard roles); and abbreviated repeat simulation (reversed roles, i.e., basic life support provider performing ALS tasks). Control teams used standard OHCA protocols and equipment (with high-performance cardiopulmonary resuscitation training intervention); for second and third simulations, experimental teams performed chest compression, defibrillation, airway, pulmonary ventilation, vascular access, medication, and transport tasks with goal-directed protocol and resuscitation-automating devices. Videorecorders and simulator logs collected resuscitation data. Results: Ten control and 10 experimental teams comprised 20 EMT-B's; 1 EMT-I, 8 EMT-C's, and 11 EMT-P's; study groups were not fully matched. Both groups suboptimally performed chest compressions and ventilations at baseline. For their second simulations, control teams performed similarly except for reduced on-scene time, and experimental teams improved their chest compressions ( P =0.03), pulmonary ventilations ( P <0.01), and medication administration ( P =0.02); changes in their performance of chest compression, defibrillation, airway, and transport tasks did not attain significance against control teams' changes. Experimental teams maintained performance improvements during reversed-role simulations. Conclusion: Simulation-based investigation into OHCA resuscitation revealed considerable variability and improvable deficiencies in small EMS teams. Goal-directed, automation-assisted OHCA management augmented select resuscitation bundle element performance without comprehensive improvement. Abstract : Supplemental digital content is available in the text.